O pontecial da mamoneira (Ricinus Communis L.) para a exploração apícola: produção, toxidez e qualidade de mel e pólen - Milfont, Marcelo de Oliveira (2007)
The research was carried out in the Núcleo de Produção Comunitária Santa Clara, belonging to the company Brasil Ecodiesel, in the county of Canto do Buriti, state of Piauí, Brazil, from May to July 2006. Laboratorial analyses were carried out in the laboratories of Universidade Federal do Ceará, Universidade de Fortaleza, Grupo Edson Queiroz and Instituto Centro de Ensino Tecnológico (CENTEC). The experiments aimed to assess the possibility of aggregating value to castor bean (Ricinus communis) plantations placing honey bee (Apis mellifera) colonies in the area. The following aspects were investigated: colony development in castor bean plantations; potential of castor bean plantations for honey production; possible toxicity of castor bean pollen and/or nectar to honey bees and humans; physical-chemical and organoleptic characteristics of castor bean honey and its commercial potential. Results showed that castor bean plantations offer good conditions for development of A. mellifera colonies because it provides pollen and nectar which are readily used by honey bees; castor bean showed to be an important nectar source for beekeeping leading in only 49 days to an average production between 18.82 (apiary in area of castor bean clean cultivation) and 23.52 kg (apiary in area of castor bean with wild weeds), similar to the annual national mean production; castor bean pollen and nectar are not toxic to honey bees or mammals, suggesting that, probably, are also adequate for human consumption. Castor bean honey presents physical-chemical characteristics within the Brazilian regulations for honey, and its organoleptic characteristics were well rated by population in test trials suggesting commercial potential. It was concluded that beekeeping in castor bean plantations can improve the area profitability, contribute to mitigate ecological impacts caused by agriculture, besides generating a natural, nutritive and well accepted product by the population.